Efficacy and mechanism of cyprosulfamide in alleviating the phytotoxicity of clomazone residue on maize seedling - Sun, Lanlan; Zhang, Chen; Xu, Hongle; Su, Wangcang; Xue, Fei; Leng, Qiuli; Niu, Yujia; Lu, Chuantao; Wu, Renhai (Frontiers in Plant Science, 2024)
IntroductionThe residues of clomazone (Clo) can lead to phytotoxic symptoms such as foliar bleaching, reduced plant height, and decreased maize yields. Herbicide safener represent one of the most economically efficient strategies for mitigating herbicide-induced damage.MethodsIn this study, various seed treatments were implemented, including the immersion of maize seeds in water (CK), immersion in Cyprosulfamide (CSA), soil supplemented with clomazone (ClO) and CSA+ClO, evaluated physiological indicators, chlorophyll content, and qRT-PCR analyses of the maize plants were evaluated under the different treatments.Results and discussionThe objective of this study was to investigate the impact of CSA on mitigating residual damage caused by Clo on maize and elucidate its mechanism. Compared to the CK, treatment with Clo resulted in significant inhibition of maize plant height, fresh weight, chlorophyll content, and carotenoid levels by 19.0%, 29.9%, 92.5%, and 86.3% respectively. On the other hand, under CSA+Clo treatment, milder inhibition was observed with reductions of only 9.4% in plant height and 7.2% in fresh weight, as well as decreases of 35.7% and 21.8% respectively in chlorophyll and carotenoid contents. The findings revealed that the application of CSA effectively mitigated the inhibitory effects of Clo residues on maize plant height, fresh weight, carotenoids and chlorophyll content. Additionally, the combination of CSA and Clo reduced MDA levels by 13.4%, increased SOD activity by 9.7% and GST activity by 26.7%, while elevating GSSG content by 31.3% compared to Clo alone, ultimately mitigating oxidative damage in maize plants. qRT-PCR analysis showed that the expression of five P450 genes (CYP72A5, CYP81A4, CYP81Q32, CYP81A9, CYP81A36), nine GST genes (GST30, GST31, GSTIV, GSTVI, GST21, GST7, GST37, GST25, IN2-1), and two UGT genes (UGT76C2, UGT83A1) significantly high increased by 6.74-, 10.27-, 4.98-, 10.56-, 25.67-, 16.70-, 46.92-,7.53-, 5.10-, 238.82-, 143.50-, 4.58-, 31.51-, 39.3-, 4.20-, 10.47-fold after CSA+Clo treatment compared to that in the Clo treatment. The pre-treatment of CSA led to the upregulation of five P450 genes, nine GST genes, and two UGT genes, which may be associated with the metabolism of Clo in maize. Overall, this study suggests that CSA could be effectively mitigates Clo residual damage by up-regulating detoxification-related genes, enhancing chlorophyll content and activities of antioxidant enzymes.